The Effect of Providing People's Business Credit (Kur) Bri Palattae Unit on Increasing the Income of MSMEs in Lalepo Village, Kahu District, Bone Regency - Juhardi (Pustaka Digital Indonesia, 2023)
This research aims to find out whether the provision of BRI Palattae People's Business Credit (KUR) has an effect on increasing MSME income in Lalepo Village, Kahu District, Bone Regency.